2020
DOI: 10.1002/anie.202002935
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Separation with MXene Membranes Based on Regularly Stacked High‐Aspect‐Ratio Nanosheets

Abstract: The uncontrolled release of antibiotics and pharmaceuticals into the environment is aw orldwide increasing problem. Thus,h ighly efficient treatment technologies for wastewater are urgently needed. In this work, seven kinds of typical antibiotics (including water and alcohol soluble ones) are successfully separated from the corresponding aqueous and ethanolic solutions using highly regular laminated membranes. Our membranes are assembled with 2-4 mmt itanium carbide nanosheets.T he solvent permeance through su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(83 citation statements)
references
References 50 publications
6
73
0
4
Order By: Relevance
“…This protein was used for dynamicm ulticolor la-beling, [8] for the development of split fluorescent reporter, [9] to investigate the dynamico fe xported bacterial proteins [10] and recently,u sing mutagenesis, the color pallet of this tag has been expanded. [11] Various rhodaninesa re usually used as fluorogensfor this protein (Figure1B);however,wehave previously shown that benzylidene imidazolones (BDI)-derivatives of GFP chromophore can also be used for this purpose (Figure 1C,D ). [12] These derivatives, as well as rhodanines, exhibit extremelyw eak fluorescencei ns olution [13] and acquire it only upon conformational fixation of the arylidenem oiety,i nduced eitherb ya ni nternal bridge or by an external action.…”
mentioning
confidence: 99%
“…This protein was used for dynamicm ulticolor la-beling, [8] for the development of split fluorescent reporter, [9] to investigate the dynamico fe xported bacterial proteins [10] and recently,u sing mutagenesis, the color pallet of this tag has been expanded. [11] Various rhodaninesa re usually used as fluorogensfor this protein (Figure1B);however,wehave previously shown that benzylidene imidazolones (BDI)-derivatives of GFP chromophore can also be used for this purpose (Figure 1C,D ). [12] These derivatives, as well as rhodanines, exhibit extremelyw eak fluorescencei ns olution [13] and acquire it only upon conformational fixation of the arylidenem oiety,i nduced eitherb ya ni nternal bridge or by an external action.…”
mentioning
confidence: 99%
“…S2, ESI †), as the peak at 39° for (104) planes disappeared and the diffraction peak for (002) planes shifted to lower angles after etching. 24 High-resolution transmission electron microscope (HRTEM) image identifies the high crystallinity and structure integrity of monolayer Ti 3 C 2 T x nanosheets (Fig. S3, ESI †).…”
mentioning
confidence: 99%
“…6 Å, as calculated from Figure 2 d, which is smaller than all of the hydrated metal ionic diameters [13] . The ion concentration on the permeate side increases linearly with the testing time, which further reveals the size‐selective exclusion of the MXene@PSS composite membrane (Figure S17) [19, 26] . In addition, from a previous report, [27] the hydration energy of Mg 2+ (−1922 kJ mol −1 ) is much larger than that of monovalent metal ions with smaller sizes (K + : −321 kJ mol −1 , Na + : −405 kJ mol −1 , and Li + : −515 kJ mol −1 ), resulting in a higher dehydration barrier to entry into the narrow interlayer spacing.…”
Section: Figurementioning
confidence: 54%
“…The uniform distribution of S indicates the homogeneous insertion of PSS in channels (Figure 2 c and Figure S7). The laminated architecture with narrow spacing (Figure 2 d) not only provides the prerequisites for the precise transportation of ions but also overcomes the notorious trade‐off effect between selectivity and permeability in many other types of membranes [19] . EDX results (Table S1) and etching X‐ray photoelectron spectroscopy (XPS) analysis (Figure S8 and Tables S2 and S3) show that the Ti/C ratio of 3:2 conforms to the theoretical structure, [20] and the EDX results of the MXene@PSS composite membrane verify the existence of sulfur (Figure S9).…”
Section: Figurementioning
confidence: 99%